Spontaneous Disappearence of Common Bile Duct Lithiasis,: Confirmed by Radiology - Piñeyro, Alberto; Yannicelli, Bernardo; Bowley, Roberto (Cirugía del Uruguay, 1981)
A case of spontaneous disappearence of common bile duct lithiasis through the normal biliary canal's is sup• ported by X - rays. Brief review of subject